NGHIÊN CỨU ĐẶC ĐIỂM DỊCH TỄ VÀ DI TRUYỀN CỦA LIÊN CẦU KHUẨN GÂY TAN MÁU β LƯU HÀNH Ở HỌC SINH TIỂU HỌC MỘT SỐ VÙNG MIỀN CỦA VIỆT NAM - Phạm, Khắc Linh; A.V., Dmitriev; Vũ, Hoàng Giang; Vũ, Thị Loan; Võ, Viết Cường; A.G., Nosik; Iu.Iu, Ilyasov (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EPIDEMIOLOGICAL AND GENETICAL CHARACTERISTICS OF β HEMOLYTIC STEPTOCOCCI IN PRIMARY SCHOOL PUPILS IN SOME AREAS OF VIETNAMBeta hemolytic streptococci group A, C and G are bacteria that cause pharyngitis, lymphadenitis, pyoderma, erysipelas, toxic shock syndrome, etc which are commonly appeared in children of different ages. In order to study the epidemiological and genetical characteristics of β hemolytic steptococci in primary school pupils in some areas of Vietnam, a total of 1450 primary school pupils including 734 males (50.62%) and 716 females (49.38%) representing for six provinces of Vietnam was investigated. The results showed that the beta hemolytic streptococci infection rate in primary school pupils was 9.38%, in which group A, group C, and group G were 3.45%, 0.55%, and 5.38%, respectively. The highest and lowest rate of streptococcal infection rate was in Quang Tri (25.5%) and Tay Ninh (4.67%) respectively. Chronic pharyngitis and tonsillitis contributed to the increment of streptococcal infection. The 11 emm types of S. pyogenes strains were identified and it hypothesized that the different existence were caused by the diversity of genotypes in various geographical regions. Genetical diversity of S. anginosus strains has been detected based on toxic genes.